Regional Government Authority Regarding Mineral and Coal Mining Business Licenses in Indonesia based on Law Number 3 of 2020 - Rina Andriani; Sulaiman Kurdi (Interdisciplinary Explorations in Research Journal, 2024)
Abstract Mineral and Coal Mining, which is a source of state income, is specifically regulated in Law Number 3 of 2020, which is a new regulation on mineral and coal mining. The purpose of this research is to review the issue of mining business permits which previously belonged to the district or city regional government which later became the authority of the central government, namely Article 35 Paragraph (1). This research uses a normative legal approach through library research with legal literature and documents. The results of this research show that the authority of regional governments in managing mining in their regions is given limitations because in carrying out management there are many problems that arise when regional governments, especially district/city regional governments, issue mining business permits, such as corruption and overlapping business permits so that district governments With the enactment of this law, cities do not have any authority, while the provincial government has the authority to grant permits related to mining which is delegated by the central government. Keywords: Authority, Licensing, mineral and coal mining, Abstrak Pertambangan Mineral dan Batubara yang menjadi salah satu sumber pendapatan negara secara khusus di atur dalam Undang-Undang Nomor 3 Tahun 2020 yang merupakan regulasi baru pertambangan mineral dan batubara. Penelitian ini bertujuan untuk meninjau mengenai persoalan izin usaha pertambangan yang sebelumnya berada pada pemerintah daerah kabupaten/kota yang kemudian menjadi kewenangan pemerintah pusat yaitu Pasal 35 Ayat (1). Penelitian ini menggunakan pendekatan hukum normatif melalui studi pustaka dengan literatur dan dokumen hukum. Hasil penelitian ini menunjukan bahwa kewenangan dari pemerintah daerah dalam mengelola pertambangan didaerahnya diberikan batasan-batasan karena dalam melakukan pengelolaan terdapat banyak masalah yang muncul ketika pemerintah daerah khususnya pemerintah daerah kabupaten/kota yang memiliki wewenang untuk mengeluarkan izin usaha pertambangan seperti korupsi dan tumpang tindih izin usaha sehingga pemerintah kabupaten/kota dengan berlakunya undang-undang ini tidak memiliki kewenangan apapun, sedangkan pemerintah provinsi memiliki kewenangan pemberian izin terkait pertambangan yang didelegasikan oleh pemerintah pusat. Kata Kunci: Wewenang, Perizinan, Pertambangan Mineral dan Batubara,